Analysis of Growth in the Agricultural Sector in the Angek Water Vegetable Producing Area, X Koto District, Tanah Datar Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The aim of this study is to analyze the growth of the agricultural sector in the Angek Water Vegetable Producing Area, X Koto District, Tanah Datar Regency. The method used in this study is descriptive with a qualitative approach. Data collection techniques used observation and interviews. From the data analysis conducted, the research results show that Aia Angek's natural resources are rich in natural resources, especially vegetables, and good soil conditions provide a comparative advantage for agriculture in the area. In addition, the role of a skilled and qualified workforce in increasing production productivity and efficiency is also an important factor. The market acts as a bridge between agricultural producers and consumers, and has a direct impact on the sustainability and growth of the agricultural sector. Investments in transportation and logistics infrastructure, access to market information, and building strong partnerships are important strategies to increase market access for farmers and agricultural producers. Through Weber's location theory framework, this study also explains the relationship between these factors and the location of the agricultural industry in Aia Angek.